THE LEGALITY OF THE EXISTENCE OF POLICE DETENTION CENTERS IN THE REPUBLIC OF INDONESIA THAT ARE NOT UNDER THE DIRECTORATE GENERAL OF CORRECTIONS - Abdul Kadir; Byrant Jibrilla Hamara (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This research analyzes the legality of detention centers operated by the Indonesian National Police (Polri) that are not affiliated with the Directorate General of Corrections (Ditjen PAS) and assesses their impact on the protection of detainees' rights. The study is motivated by the discrepancy between legal provisions, which place detention management authority under Ditjen PAS, and the reality that Polri continues to operate its own detention facilities outside the official structure. Using a normative-empirical legal method, this research combines a normative juridical analysis of relevant laws and regulations with empirical data gathered through interviews with officials from Ditjen PAS and the Metro Jaya Regional Police, field observations, and documentation review. The findings indicate that de jure, detention center management falls under the authority of Ditjen PAS as stipulated in Government Regulation No. 27 of 1983, Law No. 22 of 2022, and Ministerial Decree No. M.01.PR.07.03 of 2007. However, de facto, Polri continues to manage detention centers based on its investigative authority, creating legal ambiguity. This situation results in non-uniform service and facility standards, weak centralized oversight, obstacles to prisoner data integration, and suboptimal rehabilitation and reintegration programs, ultimately undermining the protection of detainees' rights. The study concludes that regulatory harmonization and stronger coordination between Polri and Ditjen PAS are necessary to ensure all detention facilities have a clear legal basis and can guarantee the protection of detainee rights in accordance with correctional principles.